The South African chartered accountant academic: Motivations and challenges when pursuing a doctoral degree. Issue 2 (4th June 2018) - de Jager, Phillip; Lubbe, Ilse; Papageorgiou, Elmarie
Abstract : Purpose: Accounting academics in the South African system understand their primary responsibility to be the teaching of prospective Chartered Accountants (CAs) rather than the advancement of knowledge through research. The purpose of this study is to determine what factors motivate accounting academics who are CAs to obtain doctorates in an environment dominated by the profession, where promotion is possible to Full Professor without a Doctorate but not without the professional qualification of CA. And did these doctoral CAs face challenges on their journey, such as resistance from colleagues? Design/methodology/approach: A total of 22 academic CAs with doctorates and 18 academic CAs studying towards doctorates were surveyed to gain a deeper understanding of who they are, what their motivations were for undertaking the doctorate journey and what they experienced. Findings: The main finding of this study is that the culture of accounting departments in South Africa is beginning to shift from being teaching orientated towards being more research orientated. The CAs are pursuing doctorates for the purpose of career progression and for intrinsic personal reasons. The main challenges that they faced on their journey were finding the time for family and a social life and a lack of support from colleagues and their institution. However, support seems to be improving. Research limitations/implications: The change to a research-orientated culture in South African departments of accounting, as envisioned by Van der Schyf (2008 ), is only now starting to take place. These CAs with doctorates provide evidence of that change. Originality/value: The value of this study is to provide accounting academics and the profession with a better understanding of, and a greater sensitivity to, accounting academics operating under the influence of the South African Institute of Chartered Accountants (SAICA). The study also adds to the limited amount of literature on the motives and experiences of doctoral students, especially accounting doctoral students.